Design and fabrication of wafer-scale highly uniform silicon nanowire arrays by metal-assisted chemical etching for antireflection films - Chuhao Yao (Elsevier, 2021)
We present a novel and facile scheme for fabricating wafer-scale arrays of highly uniform vertically aligned silicon nanowires (Si-NWs) in the diameter range of 50 to 200 nm. The key idea is to fabricate thin gold (Au) nanostructures using magnetron sputtering followed by de-wetting of Au and subsequent realization of wafer-scale and highly uniform Si-NWs arrays by metal-assisted chemical etching in low temperature (2 °C) without resorting to complex photolithography. The excellent properties of these Si-NWs arrays were also demonstrated numerically. A maximum exciton generation rate of 1.76 × 1024 and a maximum energy generation rate of 28 can be obtained from Si-NWs arrays with the diameter of 200 nm. The reflectivity of the Si-NWs arrays is declined with decreasing annealing temperature and is below 10% over a wide wavelength range at the annealing temperature of 200 °C. Our work provides a promising approach for constructing Si-NWs arrays with good photoelectric conversion performance.